Conceptualizing self-organization in urban planning: turning diverging paths into consistency - Boonstra, Beitske; Rauws, Ward (AESOP, 2017)
Within the realm of urban studies and spatial planning, the concept of self-organization receives increasing attention in understanding spatial transformations and related planning interventions (De Roo et al, 2012; Portugali, 2011). In exploring the potential of self-organization, various scholars however introduce diverging interpretations of the concept, consequentially leading to different understandings of what the concept can offer to planners. In the first part of the paper, we show that the different interpretations have their foundation in two distinct epistemic positions: One is a critical-realist interpretation of complex adaptive systems (Byrne, 2005), resulting in a planning focused on pattern recognition and formulating guiding conditions (Portugali, 2011; Rauws, 2015). The other includes a poststructuralist interpretation of emerging assemblages (Cilliers, 1998; DeLanda, 2006), leading to a planning focused on personal style and situational behavior (Boonstra, 2015). The potential synergies between the two epistemic positions has so far remained unexplored, while aspects of both perspectives simultaneously are at work in spatial transformations. Therefore, the second part of the paper explores their complementarity and discusses how to turn the two positions into consistency with one another – meaning how they can mutually reinforce each other without losing their individual epistemic strengths. Based on this exploration we suggest planners to act adaptively and differentiate in style in response to the situation at stake, among others by means of pattern recognition. On a conceptual level the paper shows how planning scholars can make sense of the diversity of ongoing processes of self-organization in the context of spatial transformations.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017